Nurse rock microclimates significantly buffer exposure to freezing temperature and moderate summer temperature. (June 2020) - Conver, Joshua L.; Yarwood, Elliott; Hetherington, Lucas D.; Swann, Don E.
Abstract: Nurse tree canopies mitigate exposure to freezing temperatures that could result in injury or mortality to the saguaro cactus ( Carnegiea gigantea ). Abiotic objects have been hypothesized to provide similar beneficial microclimates. We used data loggers at 11 nurse rock sites to record daily daytime summer maximum and winter nighttime minimum temperatures at Saguaro National Park, Arizona, to examine the effectiveness of rocks to moderate seasonal temperature extremes in the microclimate. Temperatures at rock sites averaged 2 °C warmer than exposed open control sites in winter. We found that the efficiency of rocks to act as insulators significantly increased as temperature at control sites decreased, consistent with studies of tree canopies, and that the insulation effect lasted throughout the night. In summer, rocks reduced exposure to maximum temperatures but did not offer significantly more cooling at higher temperatures. Our results suggest that the protection from freezing temperature offered by rocks in winter is more ecologically beneficial to the saguaro than extreme temperature amelioration during summer in the cold-limited frontiers of the species' range. Highlights: Nurse rocks significantly mitigated exposure to freezing temperatures in winter. This benefit is shared by nurse trees and rocks. Rocks did not provide significantly more cooling at higher temperatures in summer. Rock cavities were cooler on average in summer than the open, exposed environment.